Surface mechanical properties of comet 67P. (13th June 2019) - Arnold, W.; Fischer, H.-H.; Knapmeyer, M.; Krüger, H.
Abstract: We give an overview of the mechanical properties of the surface material of comet 67P/Churyumov–Gerasimenko, as measured with the Surface Electric Sounding and Acoustic Monitoring Experiment instruments within the Rosetta/Philae mission. The data yielded information on the compression strength and the elastic modulus of the surface material and of dust particles.